Community-Based Participatory Research in Action: The Patient-Centered Medical Home and Neighborhood. (November 2020) - Williams-Livingston, Arletha; Henry Akintobi, Tabia; Banerjee, Ananya
Background: The Morehouse School of Medicine Patient Centered Medical Home and Neighborhood Project was developed to implement a community-based participatory research driven, integrated patient-centered medical home and neighborhood (PCMH) pilot intervention. The purpose of the PCMHN was to develop a care coordination program for underserved, high-risk patients with multiple morbidities served by the Morehouse Healthcare Comprehensive Family Health Clinic. Measures: A community needs assessment, patient surveys and provider interviews were administered. Results: Among a panel of 367 high-risk patients and potential participants, 93 participated in the intervention and 42 patients completed the intervention. The patients self-reported increased utilization of community support, increased satisfaction with health care options, and increased self-care management ability. Conclusion: The results were largely attributable to the efforts of community health workers and targeted community engagement. Lessons learned from implementation and integration of a community-based participatory approach will be used to train clinicians and small practices on how to affect change using a care coordination model for underserved, high-risk patients emphasizing CBPR.